Ecological services performed by the bonobo (Pan paniscus): seed dispersal effectiveness in tropical forest. (20th September 2013) - Beaune, David; Bretagnolle, François; Bollache, Loïc; Bourson, Chloé; Hohmann, Gottfried; Fruth, Barbara
Abstract: Survival of Afrotropical primary forests depends not only on habitat protection but also on the protection of animal species such as frugivorous primates, recognized as the most important seed dispersers for many plants. Here we investigate seed-dispersal services by the bonobo ( Pan paniscus ) in an evergreen lowland tropical rain forest of the Congo Basin. In the long-term research site of LuiKotale, we investigated food habits and seed processing based on 22 mo of behavioural observation, seed trial experiment and long-term daily GPS tracking of a habituated ape community. Bonobos were mainly frugivores (66% of all feeding sessions), spending about 3.5 h d −1 swallowing seeds that were transported for an average of 24 h in the gut. On average, an individual bonobo dispersed 172 kg y −1 of seeds (or 220000 seeds y −1 ) of more than 91 plant species by endozoochory over an average distance of 1.2 km from the parent tree. Passed seeds germinated more rapidly, more successfully and had greater post-dispersal survival than unpassed seeds. Bonobo-dispersed plants accounted for 40% of tree species and 65% of individual trees in the study site (12 1-ha plots census). Since bonobos show little functional overlap with other frugivores, the loss of their seed-dispersal services is likely to affect forest structure and dynamics. Our results justify description of the threatened bonobo as a gardener of the Congo forest.